Integral mission and drug abuse in a changing landscape : mobilizing the United Church of Christ in the Philippines together towards life - Tibus, Van Cliburn M. (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.